All Hands on Deck: A synchronized whole-of-world approach for COVID-19 mitigation - Ebrahim, Shahul H. (Int J Infect Dis, 2020)
The COVID-19 pandemic can no longer be mitigated by a nationwide approach of individual nations alone. Given its scale and accelerating expansion, COVID-19 requires a coordinated and simultaneous Whole- of-World approach that galvanizes clear global leadership and solidarity from all governments of the world. Considering an ‘all hands-on deck’ concept, we present a comprehensive list of tools and entities responsible for enabling them, as well a conceptual framework to achieve the maximum impact. The list is drawn from pandemic mitigation tools developed in response to past outbreaks including influenza, coronaviruses, and Ebola, and includes tools to minimize transmission in various settings including person-to-person, crowd, funerals, travel, workplace, and events and gatherings including business, social and religious venues. Included are the roles of individuals, communities, government and other sectors such as school systems, health, institutions, and business. While individuals and communities have significant responsibilities to prevent person-to-person transmission, other entities can play a significant role to enable individuals and communities to make use of the tools. Historic and current data indicate the role of political will, whole-of-government approach, and the role of early introduction of mitigation measures. There is also an urgent need to further elucidate the immunologic mechanisms underlying the epidemiological characteristics such as the low disease burden among women, and the role of COVID-19 in inducing Kawasaki-like syndromes in children. Understanding the role of and development of anti-inflammatory strategies based on our understanding of pro-inflammatory cytokines (IL1, IL-6) is also critical. Similarly, the role of oxygen therapy as an anti-inflammatory strategy is evident and access to oxygen therapy should be prioritized to avoid the aggravation of COVID-19 infection. We highlight the need for global solidarity to share both mitigation commodities and infrastructure between countries. Given the global reach of COVID-19 and potential for repeat waves of outbreaks, we call on all countries and communities to act synergistically and emphasize the need for synchronized pan-global mitigation efforts to minimize everyone's risk, to maximize collaboration, and to commit to shared progress.